Motivasi Kerja dan Kinerja Karyawan: Tinjauan Sistematis Peran Kepuasan Kerja dalam Perspektif Psikologi Manajemen - Moch. Wildani Dwi Sulaiman; Nur Khasanah; Faidhiyatul Muna Iza; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Work motivation, job satisfaction, and employee performance are key aspects of management psychology that continue to evolve as organizational productivity demands increase. In an era of global competition, organizations are required to manage human resources effectively by enhancing work motivation and job satisfaction to achieve optimal performance. This study aims to examine the relationship between work motivation and employee performance, as well as to analyze the role of job satisfaction as a mediating variable in that relationship. The method used is a literature review with a qualitative approach. Data were collected through the Google Scholar and Publish or Perish databases using keywords related to work motivation, job satisfaction, and employee performance from a management psychology perspective. From 25 articles found between 2022 and 2026, 5 of the most relevant articles were selected for further analysis.The results of the study indicate that work motivation has a significant influence on employee performance, both directly and indirectly through job satisfaction as a mediating variable. Additionally, there is a growing trend toward the integration of management psychology approaches in efforts to enhance employee performance. Thus, it can be concluded that the simultaneous management of motivation and job satisfaction is a key factor in achieving optimal performance. Further research is recommended to develop a more comprehensive and integrative model.